Everyday Health among Older People: A Comparison between Two Countries with Variant Life Conditions. (10th August 2017) - Fagerström, Cecilia; Wranker, Lena Sandin; Kabir, Zarina Nahar; Sternäng, Ola
Abstract : This study described health factors of importance for everyday health, such as pain, tiredness, and sleeping problems, in a cross-national context. Data for persons 60+ years were obtained from the Poverty and Health in Aging study, Bangladesh, and the Swedish National Study on Aging and Care-Blekinge. The strongest associations with everyday health in Sweden were found for pain and tiredness, while in Bangladesh they were financial status, tiredness, and sleeping problems. As similarities were found regarding the associations of tiredness on everyday health, tiredness may be a universal predictor of everyday health in older adults irrespective of country context.